2006
DOI: 10.1088/0957-0233/17/5/s31
|View full text |Cite
|
Sign up to set email alerts
|

Fibre gratings for hydrogen sensing

Abstract: Liquid hydrogen has been intensively used in aerospace applications for the past 40 years and is of great interest for future automotive applications. Following major explosive risks due to the use of hydrogen in air, several studies were carried out in order to develop optical fibre sensors for the detection of hydrogen leakage. This paper aims at the presentation of new hydrogen sensors based on the use of fibre Bragg gratings (FBG) and long period gratings (LPG) coated by palladium nanolayers. The sensing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…We observed a drift in the signal of approximately 2% in the devices that were exposed several times to hydrogen. Such a drift is mainly due to the instability of the Pd thin film resulting from the large volume changes that occur during the hydrogenation of the film [16][17][18][19][20][21][22][23][24][25][26][27][28]. The drift may become higher with time or after many times loading and un-loading of hydrogen, which can severely affect the reliability of the sensor.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed a drift in the signal of approximately 2% in the devices that were exposed several times to hydrogen. Such a drift is mainly due to the instability of the Pd thin film resulting from the large volume changes that occur during the hydrogenation of the film [16][17][18][19][20][21][22][23][24][25][26][27][28]. The drift may become higher with time or after many times loading and un-loading of hydrogen, which can severely affect the reliability of the sensor.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard the structure shown in Fig. 1 is better than core-exposed, D-shape, or tapered optical fibers since its fabrication does not require chemical etching, polishing, or tapering the fibers that usually weakens them [18][19][20][21][22][23][24][25][26][27][28]. The losses caused by the insertion of the single-mode fiber between two multimode fibers are typically below 5 dB (measured at 850 nm).…”
Section: Sensor Fabrication and Operation Principlementioning
confidence: 99%
See 2 more Smart Citations
“…Once coated with sensing material on the cladding at the grating region, upon the change of refractive index, the LPFGs can serve as a gas or liquid sensor and show very good sensitivity towards the target materials [16][17][18][19]. In 2006, Trouillet et al [16] reported the use of the Pd-coated LPFGs as a hydrogen sensor. In their work, Pd was deposited on one side of the optical fiber, which was modified into LPFGs.…”
Section: Introductionmentioning
confidence: 99%